FKBP12 Controls Aspartate Pathway Flux in Saccharomyces cerevisiae To Prevent Toxic Intermediate Accumulation - Arévalo-Rodríguez, Miguel (American Society for Microbiology, 2004)
FKBP12 is a conserved member of the prolyl-isomerase enzyme family and serves as the intracellular receptor for FK506 that mediates immunosuppression in mammals and antimicrobial actions in fungi. To investigate the cellular functions of FKBP12 in Saccharomyces cerevisiae, we employed a high-throughput assay to identify mutations that are synthetically lethal with a mutation in the FPR1 gene, which encodes FKBP12. This screen identified a mutation in the HOM6 gene, which encodes homoserine dehydrogenase, the enzyme catalyzing the last step in conversion of aspartic acid into homoserine, the common precursor in threonine and methionine synthesis. Lethality of fpr1 hom6 double mutants was suppressed by null mutations in HOM3 or HOM2, encoding aspartokinase and aspartate β-semialdehyde dehydrogenase, respectively, supporting the hypothesis that fpr1 hom6 double mutants are inviable because of toxic accumulation of aspartate β-semialdehyde, the substrate of homoserine dehydrogenase. Our findings also indicate that mutation or inhibition of FKBP12 dysregulates the homoserine synthetic pathway by perturbing aspartokinase feedback inhibition by threonine. Because this pathway is conserved in fungi but not in mammals, our findings suggest a facile route to synergistic antifungal drug development via concomitant inhibition of FKBP12 and Hom6.